Rubber Trees Demonstrate a Clear Retranslocation Under Seasonal Drought and Cold Stresses - Li, Yuwu; Lan, Guoyu; Xia, Yujie (Frontiers in Plant Science, 2016)
Having been introduced to the northern edge of Asian tropics, the rubber tree (Hevea brasiliensis) has become deciduous in this climate with seasonal drought and cold stresses. To determine its internal nutrient strategy during leaf senescence and deciduous periods, we investigated mature leaf and senescent leaf nutrients, water-soluble soil nutrients and characteristics of soil microbiota in nine different ages of monoculture rubber plantations. Rubber trees demonstrate complicated retranslocation of N, P, and K during foliar turnover. Approximately 50.26% of leaf nutrients and 21.47% of soil nutrients were redistributed to the rubber tree body during the leaf senescence and withering stages. However, no significant changes in the structure- or function-related properties of soil microbes were detected. These nutrient retranslocation strategy may be important stress responses. In the nutrient retranslocation process, soil plays a dual role as nutrient supplier and nutrient “bank.” Soil received the nutrients from abscised leaves, and also supplied nutrients to trees in the non-growth stage. Nutrient absorption and accumulation began before the leaves started to wither and fall.